Qualitative Study on Dialogic Literary Gatherings as Co-creation Intervention and Its Impact on Psychological and Social Well-Being in Women During the COVID-19 Lockdown - Ruiz-Eugenio, Laura; Toledo del Cerro, Ana; Gómez-Cuevas, Sara; Villarejo-Carballido, Beatriz (Frontiers in Public Health, 2021)
Background: Dialogic Literary Gatherings (DLG) are evidence-based interventions implemented in very diverse educational and health settings. The main elements that make DLG a co-creation intervention and promote health during the COVID-19 crisis lockdown are presented. This study focuses on the case of a DLG that is being promoted by an adult school in the city of Barcelona. Methods: This qualitative study was conducted using a communicative approach. Seven in-depth interviews with participants in the online DLG have been conducted. Five of them are women without higher education ranging from 56 to 85 years old and two are educators of this school. Results: The main results are 2-fold. First, the factors that make DLG a co-creation intervention, such as egalitarian dialogue and dialogical creation of knowledge in the decision-making process, are found. Second, the results show how DLG is contributing to creating a supportive environment that breaks the social isolation of confinement and improving the participants' psychological and social well-being. Conclusions: The findings from this study contribute to generating knowledge about a co-creation process between adult education participants and educators in education and health promotion during the COVID-19 lockdown, which could be replicated in other contexts.